Data Aided Channel Estimation for MIMO-OFDM Wireless Systems Using Reliable Carriers - Khan, Inaamullah; Cheffena, Michael; Hasan, Mohammad Mahmudul (IEEE access, 2023)
Wireless channel estimation is one of the challenging problems in multiple input multiple output orthogonal frequency division multiplexing (MIMO-OFDM) wireless systems. The MIMO-OFDM exploits the spatial resources and increases the reliability and capacity of wireless systems. However, the performance of these systems depends on accurate channel estimation since the receivers require perfect channel state information (CSI) for coherent signal detection. Thus, wireless channel estimation is a necessary component of OFDM systems. In this article, we have proposed an algorithm for MIMO-OFDM systems that combines pilot symbols with reliable data symbols for channel estimation. The reliable data symbols serve as virtual pilots and enhance the spectral efficiency of the system. The proposed data aided channel estimation (DACE) algorithm eliminates the requirement of any additional resources such as excessive number of training sequences to attain the desired performance. Also, it outperforms the traditional least square (LS) and linear minimum mean square error (LMMSE) methods for channel estimation in terms of mean square error (MSE) and bit error rate (BER) performance of the system.